Control of the illegal use of clenbuterol in bovine production - Cristino, Assunção (2003)
This study is based on a plan of collecting different matrices (hair, eye, muscle, liver and kidney) in order to define a strategy for the control of the illegal use of clenbuterol in bovine production. Of all matrices utilised, hair is recommended for the analytical control of clenbuterol in living animals, due to its being permanently available and easy to collect. The eye, or rather the retina, is the matrix which gives the most trustworthy result, after the animal slaughter, and the one that best helps in the determination of the illegal use of clenbuterol in a perspective of gradual food safety improvement.